Pengaruh Penggunaan Silica Fume dan Serbuk Bata Merah Terhadap Kuat Tekan Bebas dan Kuat Geser Tanah Lempung - Abriari, Devina; Abduh, Muh Natsir; Sariman, Syahrul (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Clay soil has low load-bearing capacity. One method to improve this issue is by mixing chemical additives, such as silica fume and red brick powder, into the clay soil as adhesive media that can fill the soil's pores, compacting and forming a solid mass. This study aims to determine the unconfined compressive strength and shear strength of clay soil after adding silica fume and red brick powder. The method involves testing unconfined compressive and shear strength using 9% red brick powder by soil weight, along with silica fume added in varying amounts of 5%, 10%, and 15%. Three samples are prepared for the original soil and each composition used. The unconfined compressive strength of the original soil increased by 48.2% with the addition of 9% red brick powder, while each 5% addition of silica fume raised the compressive strength by an average of 3.1%. Similarly, shear strength increased by 33.5% in the original soil with 9% red brick powder, while each 5% silica fume addition improved it by an average of 5.4%. The addition of red brick powder and silica fume can effectively increase the compressive and shear strength of clay soil.